Bacteria Identification In Traditional Sauce (Sambal) At The Restaurants Nearby The Traditional Markei Of Gorontalo City - Ana Pepiana; Laksmyn Kadir; Agusrianto Yusuf (Journal of Health, Technology and Science (JHTS), 2021)
The unsafe food will cause the health problems in the community. Sambal which is known as the traditional sauce is a sauce made from chilies that are crushed until the water content comes out, giving it a spicy taste. Furthermore, Sambal is processed in a simple way so that it can leac to the contamination of microorganisms such as Coliform bacteria contamination. This study aims to determine the presence of Coliform bacteria contamination in Sambal at the supermarket nearby the traditional market in Gorontalo City. This research is a descriptive study using a qualitative approach. It examines the existence of Coliform bacteria using the Most Probable Number (MPN) method. The population in this study were 14 samples with the sampling technique by accidental sampling. Coliform bacteria examination results show that Sambal sample is found with positive results contaminated with Coliform bacteria, namely 11 samples with a percentage of 78.6% and negative results of 3 samples with a percentage of 21.4%. Based on the results, it can be concluded that a positive result was found consisting of 1 sample of coliform fekal bacteria, in this case the bakteri Escherchia coli. bacteria, and 10 samples from the non-fecal coliform bacteria.